Acute coronary syndrome in Behcet's disease caused by a coronary artery aneurysm and thrombosis - (:unkn) unknown (My University, 2014)
Behcet's disease (BD) is a multisystemic vasculitis that can involve vessels of all sizes and is characterized by recurrent oral and genital ulcers with variable manifestations affecting the skin, eyes, and central nervous and musculoskeletal systems. Vascular involvement in BD is reported to be up to 40% in different series. The abdominal and thoracic aorta and pulmonary and femoral arteries are the most commonly involved arteries. However coronary arteries are rarely affected. Herein, we present a 29-year-old man who was consulted with progressive severe chest pain of 3 days in duration to our clinic. The patient was diagnosed with BD with mucocutaneous symptoms and a positive pathergy test 1 year ago and was in clinical remission for the last 6 months. At the first evaluation in the emergency department, the patient's vital signs were stable, whereas he had elevated troponin T levels with a normal electrocardiogram and hypokinetic areas in the apex of the heart in the echocardiography. Conventional and computed tomography coronary angiography revealed aneurysms and intramural thrombosis in the left anterior descending and right coronary arteries. Although ischemic symptoms and signs improved with anticoagulant and antiaggregant therapies, coronary aneurysms were observed to increase in size. Immunosuppressive (IS) treatment was started with pulse intravenous corticosteroids and cyclophosphamide. Because of the high re-stenosis risk, stents were not applied to the affected vessels during the acute thrombosis period. During routine investigations, an in situ pulmonary thrombosis was also detected bilaterally in the peripheral pulmonary arteries. In conclusion, coronary artery aneurysm is a rare and poor prognostic manifestation of BD. The treatment protocol for these aneurysms is not well clarified. IS therapies are definitely indicated, but the role of anticoagulants and invasive vascular interventions is controversial.
Keywords: acute coronary syndrome; Behcet’s disease; cardiac involvement; Coronary aneurysm